+0  
 
+1
218
2
avatar

I'm sorry, but two more questions please:)

 

sin(x) - sin(x) * cos^2(x)

 

 

 

sin^4(x) - cos^4(x) divided by sin^2(x) - cos^2(x)

Guest Mar 29, 2017
Sort: 

2+0 Answers

 #1
avatar+79911 
+2

sin(x) - sin(x) * cos^2(x)  =

 

sin x  - sin x  *  ( 1 - sin^2 x)  =

 

sinx  -  sin x  + sin^3 x  =

 

sin^3 x

 

 

 

sin^4(x) - cos^4(x) divided by sin^2(x) - cos^2(x)

 

Factor   sin^4 x - cos^4x   as      

 

[sin^2 x + cos ^2 x] [ sin^2 x - cos^2 x ]  /  [sin^2 x - cos^2 x ]   =

 

sin^2 x  + cos^2 x   =

 

1

 

 

 

cool cool cool

CPhill  Mar 29, 2017
 #2
avatar+91263 
+2

sin(x) - sin(x) * cos^2(x)

\(sin(x) - sin(x) * cos^2(x)\\ =sin(x) (1- cos^2(x))\\ =sin(x) sin^2(x)\\ =sin^3(x)\\ \)

 

 

sin^4(x) - cos^4(x) divided by sin^2(x) - cos^2(x)

 

\(\frac{sin^4(x) - cos^4(x) }{sin^2(x) - cos^2(x)}\\ =\frac{(sin^2(x) - cos^2(x))(sin^2(x) + cos^2(x)) }{sin^2(x) - cos^2(x)}\\ =\frac{sin^2(x) - cos^2(x)}{sin^2(x) - cos^2(x)}\\~\\ =1 \qquad where \;\;\; x\ne \frac{\pi+2n\pi}{4} \;\;\;n\in Z\)

Melody  Mar 29, 2017

15 Online Users

avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details